Effects of nor adrenal in on the activity of stellate cells in mouse cochlear nucleus - Ramazan Bal (Eurasian Journal of Veterinary Sciences)
In this study, it was aimed to assess the effects ol noradrenalın on the stellate neuron Intracellular recordings were performed (rom stellate neurons ol mice cochlear nucleus in vitro using the whole cell patch clamp technique The resting potential of stellate neurons was -61.3 ± 3.3 milivolt (mV)Hn= 18) and input resistance was 210 21 megaOhm (Mil) (n=18). Noradrenalin (100 mikro mo! (nM)) applied in perfusion solution depolarized the resting potantial by 26.1 ±4.1 rnV (n=5). In some cells, noradrenalin caused the resting potential to shift further in depolarized potentials, resulting in being spontaneously silent. The study of voltage clamp using ramp voltage protocol indicated that potassium current decreased. In conclusion, noradrenalin increases the spontaneously occurring activity, decreasing the potassium current amplitude.